Penggunaan Komposit Layer TiO2 / SnO2 sebagai Fotoanoda pada Dye Sensitized Solar Cell: M N Fajar, R Hidayat, Triwikantoro, Endarko - M. N. Fajar M. N. Fajar; R. Hidayat R. Hidayat; Triwikantoro Triwikantoro; Endarko Endarko (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2019)
Photoanode is one component of dye-sensitive cell solar (DSSC) which synthesized from metal oxide semiconductor materials with nanoparticle size that deposited onto the transparent conductive glass. The semiconductor material used must meet several criteria such as a wide surface and a high level of porosity so that it can absorb dye properly. One modification that is often done on DSSCs was to improve its performance by applying TiO2/ SnO2 to DSSC photoanodes. In this study, the performance of the synthesized DSSC with TiO2/SnO2 composites with both single and double layers structure will be compared to the performance of the synthesized DSSC from either photoanodes with a single layer structure of TiO2 or SnO2. The results showed that the high-efficiency of the DSSC could be achieved for both TiO2 and SnO2 single layer with value at 2.12 and 2.06%, respectively.